2022
DOI: 10.3389/fimmu.2022.950782
|View full text |Cite
|
Sign up to set email alerts
|

mRNAsi-related metabolic risk score model identifies poor prognosis, immunoevasive contexture, and low chemotherapy response in colorectal cancer patients through machine learning

Abstract: Colorectal cancer (CRC) is one of the most fatal cancers of the digestive system. Although cancer stem cells and metabolic reprogramming have an important effect on tumor progression and drug resistance, their combined effect on CRC prognosis remains unclear. Therefore, we generated a 21-gene mRNA stemness index-related metabolic risk score model, which was examined in The Cancer Genome Atlas and Gene Expression Omnibus databases (1323 patients) and validated using the Zhongshan Hospital cohort (200 patients).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Weng et al found that SCG2 was a risk factor with higher expression predicting poorer prognosis, and the SCG2 high expression subgroup was the immune hot type and considered more suitable for immunotherapy [53]. Weng et al found that a generated metabolic risk score model using a 21-gene mRNA dryness index could provide a more accurate stratification of colorectal risk and screening of colorectal patients who respond to immunotherapy [54]. In our present study, we found that this risk model was also closely related to several ICGs, CRSGs, and immune cells and factors, and many chemotherapy agents differ significantly between high-and low-risk CESC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Weng et al found that SCG2 was a risk factor with higher expression predicting poorer prognosis, and the SCG2 high expression subgroup was the immune hot type and considered more suitable for immunotherapy [53]. Weng et al found that a generated metabolic risk score model using a 21-gene mRNA dryness index could provide a more accurate stratification of colorectal risk and screening of colorectal patients who respond to immunotherapy [54]. In our present study, we found that this risk model was also closely related to several ICGs, CRSGs, and immune cells and factors, and many chemotherapy agents differ significantly between high-and low-risk CESC patients.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 In 2018, Malta et al developed a mRNA expression based-index (mRNAsi) model using machine learning algorithm to evaluate the stemness of tumors. 8 Based on mRNAsi, many stemness signatures have been constructed for prognostic analysis, [9][10][11] including GC. [12][13][14] However, the absolute stemness index calculated by mR-NAsi is easily influenced by sample composition, 15 and in some cancers, including GC, contrary to previous research, higher stemness corresponds to a better prognosis.…”
Section: Introductionmentioning
confidence: 99%